Requirements Negotiation: Does Consensus Reduce Software Development Cost? - Ahmad, S.; Muda, N. A.; Muda, A. K.; Othman, Z. (AICIT, 2012)
The requirements engineering activities within a software project are known to be critical to the successful production of a correctly functioning system. This is particularly so when considering the varying views of multiple stakeholders. One promising approach for improving the outcome is to introduce formal negotiation. Negotiation is beneficial to identify and to resolve conflicts between stakeholders. Consensus achieved through negotiation represents all key stakeholders’ perspectives and perceptions regarding the system to be developed. The aim of implementing negotiation is to minimize the possibility of introducing defects during the creation of requirements and to decrease later effort required to fix requirements’ defects. This paper answers the question of whether consensus gives positive significant impact to the software project as a whole or not. It presents an approach to estimate the savings from implementing negotiation in the requirements elicitation process. An empirical evaluation study is adopted through a role play experiment to evaluate the benefit of exercising negotiation. The net gain and the return on investment show positive values which suggest that negotiation activities are worth an investment. Based on a return on investment of 197 percent on average, this paper suggests that negotiation is a useful prevention activity to inhibit defects from occurring during the requirements creation process.